Incidence and clinical impact of respiratory viruses in adults with cystic fibrosis. Issue 3 (14th October 2013) - Flight, William G; Bright-Thomas, Rowland J; Tilston, Peter; Mutton, Kenneth J; Guiver, Malcolm; Morris, Julie; Webb, A Kevin; Jones, Andrew M
Abstract : Background: Viral respiratory infection (VRI) is a common cause of pulmonary exacerbations in children with cystic fibrosis (CF). The importance of VRI in adult CF populations is unclear. Objective: To determine the incidence and clinical impact of VRI among adults with CF. Methods: One hundred adults with CF were followed up prospectively for 12 months. Sputum, nose swabs and throat swabs were collected every 2 months and at onset of pulmonary exacerbation. PCR assays for adenovirus, influenza A&B, human metapneumovirus, parainfluenza 1–3, respiratory syncytial virus and human rhinovirus were performed on each sample. Symptom scores, spirometry and inflammatory markers were measured at each visit. Results: One or more respiratory viruses were detected in 191/626 (30.5%) visits. Human rhinovirus accounted for 72.5% of viruses. Overall incidence of VRI was 1.66 (95% CI 1.39 to 1.92) cases/patient-year. VRI was associated with increased risk of pulmonary exacerbation (OR=2.19; 95% CI 1.56 to 3.08; p<0.001) and prescription of antibiotics (OR=2.26; 95% CI 1.63 to 3.13; p<0.001). Virus-positive visits were associated with higher respiratory symptom scores and greater C-reactive protein levels. Virus-positive exacerbations had a lower acute fall in FEV1 than virus-negative exacerbations (12.7% vs 15.6%; p=0.040). The incidence of exacerbations, but not VRI, was associated with greater lung function decline over 12 months (−1.79% per pulmonary exacerbation/year; 95% CI −3.4 to −0.23; p=0.025). Conclusion: VRI is common in adults with CF and is associated with substantial morbidity. Respiratory viruses are a potential therapeutic target in CF lung disease.